2019
DOI: 10.23937/2377-3634/1410107
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Autoantibodies in Sudanese Children with Newly Diagnosed Type 1 Diabetes Mellitus

Abstract: Background: Immunepositive type one diabetes mellitus is the commonest cause of diabetes in children worldwide. Seronegative cases are said to be more common among black Africans. In a previous study in Sudan 46% of cases were found to have positive GAD antibodies. Objectives of the study: The aim of this study was to find out the prevalence of pancreatic autoantibodies among multiethnic group of newly diagnosed Sudanese children by testing for multiple antibodies and to see how common are seronegative cases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…(21) In this study, the prevalence of anti-GAD65 autoantibodies was 78.7% in T1D Indonesian children in concordance with the high prevalence of anti-GAD65 in T1D children reported in Western countries, 73.2% in the US and 86% in Europe. (8) Also, these results are in line with a study in Korea that reported that 71% of T1D patients were positive for anti-GAD65 (23) and 77.5% in Sudan (24) but in contrast to previous data that the most idiopathic types are found in Asian and African countries according to low positivity autoimmune markers. (8,14) An anti-GAD65 positivity of 53% has been reported in India (9), 44.3% in Singapore, 34.1% in Syria and 49.5% in Jordan (14).…”
Section: Discussionsupporting
confidence: 87%
“…(21) In this study, the prevalence of anti-GAD65 autoantibodies was 78.7% in T1D Indonesian children in concordance with the high prevalence of anti-GAD65 in T1D children reported in Western countries, 73.2% in the US and 86% in Europe. (8) Also, these results are in line with a study in Korea that reported that 71% of T1D patients were positive for anti-GAD65 (23) and 77.5% in Sudan (24) but in contrast to previous data that the most idiopathic types are found in Asian and African countries according to low positivity autoimmune markers. (8,14) An anti-GAD65 positivity of 53% has been reported in India (9), 44.3% in Singapore, 34.1% in Syria and 49.5% in Jordan (14).…”
Section: Discussionsupporting
confidence: 87%
“…One example of an IAA is proinsulin, which is the only anti-islet antibody expressed almost exclusively in β -cells [14] and corresponds to the specific targeting of β -cells by the T-cells infiltrating the pancreatic islets. The very high frequency of IAA found in young children upon diabetes onset implied that loss of tolerance to proinsulin was common in those who progress rapidly into the disease [11, 14, 75]. IAAs were also found in a nonobese diabetic mouse model of spontaneous type 1 diabetes [13]; this further supports the role of proinsulin as a primary autoantigen, which is usually the first islet autoantibody to be detected.…”
Section: Introductionmentioning
confidence: 92%